Endovascular Retrieval of a Fractured Umbilical Arterial Catheter in a Term Infant: A Rare Complication and its Management - Benjamin Wei Liang Ng; Martin Ngie Liong Wong (Malaysian Journal of Paediatrics and Child Health, 2026)
Umbilical arterial catheters (UACs) are widely used in neonatal intensive care for haemodynamic monitoring and blood sampling. While complications such as thrombosis and infection are well recognised, catheter fracture is exceptionally rare but potentially life-threatening. We describe a term neonate with hypoxic-ischaemic encephalopathy undergoing therapeutic hypothermia who developed a UAC fracture during catheter repositioning. The retained fragment migrated into the aorta, requiring urgent retrieval. After careful planning, endovascular removal was performed via the femoral artery using a snare system. Despite technical challenges related to vascular access and sheath size, the fragment was retrieved successfully without complications. This case highlights a rare but serious complication of UAC, demonstrating the feasibility and effectiveness of endovascular retrieval as a less invasive alternative to surgery in neonates. Additionally, it underscores the importance of preventive strategies, including meticulous securement, minimising repositioning, and safe suture removal techniques, to mitigate the risk of such adverse events.